Potensi Antioksidan Buah Naga Merah (Hylocereus polyrhizus) Kering dengan Pre-Treatment - Gusti Ayu Kadek Diah Puspawati; Putu Timur Ina; Gusti Ayu Ekawati (JURNAL AGROTEKNOLOGI, 2022)
Red dragon fruit has the potential as a functional food because it contains bioactive compounds that provide health benefits. Dried fruit is a simple processing fruit method and does not change the shape of the fresh fruit much, but during the drying process, the bioactive compounds are easily damaged by heat. It is necessary to give pre-treatment before drying. The study aimed to determine the antioxidant capacity, total phenolic, total flavonoid, betacyanin levels, and sensory preference of dried red dragon fruit with pre-treatments. The six levels of pre-treatments were without pretreatment/control (K0), steam blanching (70ºC) for 10 minutes (K1), soaking in cold citric acid (3%) for 10 minutes (K2), soaking in cold citric acid (3%) for 3 minutes, then steam blanching at 70ºC for 7 minutes (K3), soaking in cold salt (5%) for 10 minutes (K4), and soaking in cold salt (5%) for 3 minutes, steam blanching at 70ºC for 7 minutes (K5), then dried it at 50ºC for 18 hours. The results showed that the control (K0) had the highest total phenolic content (20.10 mg GAE/g), total flavonoid content (5.92 mg QE/g), betacyanin content (1.57 mg/g), antioxidant capacity (1.72 mg GAEAC/g), and organoleptic preference like of color (5.65), rather like of odor (5.00), like of texture (5.69), like of taste (5.92), and like of overall acceptance (5.92). Based on sensory (organoleptic) acceptance, the steam blanching (70ºC, 10 minutes) (K1) of dried red dragon fruit had the highest preference: like of color (6.08), like of texture (5.85), like of taste (6.23), and like of overall acceptance (6.23), but rather like of odor (5.31). Meanwhile, KI had 16.71 mg GAE/g of total phenolics, 4.98 mg QE/g of total flavonoids, 0.87 mg/g of betacyanin levels, and 1.48 mg GAEAC/g of antioxidant capacity. Dried red dragon fruit (especially with steam blanching) has the potential as a functional food ingredient because the pre-treatment maintains its bioactive content during drying. Keywords: dried red dragon fruit, functional food ingredients, pre-treatment